Study on the nutritional characteristics and antioxidant activity of dealcoholized sequentially fermented apple juice with Saccharomyces cerevisiae and Lactobacillus plantarum fermentation. (30th November 2021) - Li, Hongcai; Huang, Jintao; Wang, Yaqin; Wang, Xingnan; Ren, Yichen; Yue, Tianli; Wang, Zhouli; Gao, Zhenpeng
Highlights: Sequential fermentation combined with dealcoholization can reduce the harm caused by ethanol. Sequential Saccharomyces cerevisiae – Lactobacillus plantarum fermentation endowed apple juice with more nutrition and flavor. The product of Saccharomyces cerevisiae fermentation can be used as the substrate for Lactobacillus plantarum fermentation. Sequential fermentation with different strains improves the antioxidant activity of apple juice. Abstract: For the preparation of non-alcoholic fermented apple juice products with high antioxidant activity, we evaluated the physicochemical indicators, functional components, aroma and antioxidant activity of products at different stages of Saccharomyces cerevisiae fermentation, dealcoholization, and Lactobacillus plantarum sequential fermentation. After S . cerevisiae fermentation, the total sugar was reduced by 7.46 g/100 mL and the ethanol reached 6.56% (v/v), which decreased to less than 0.50% (v/v) after dealcoholization. After L . plantarum fermentation, the viable count reached 4.26 × 10 8 CFU/mL and flavonoids increased; vitamin C and B6 levels peaked at 1.97 and 1.17 mg/100 mL respectively. Fermented by L . plantarum after dealcoholized, new volatiles were produced (propanol, citronellol, ethyl lactate and hexyl butyrate), ketones and acids were enriched; antioxidant activity was improved and had the highest free radical scavenging rate. The sequential fermentation of apple juice with S . cerevisiae, dealcoholization, and L . plantarum enriched its nutritional properties and antioxidant activity.